Summer Dormancy in Perennial Cool-Season Forage Grasses - Özlem ÖNAL AŞCI; Ömer EĞRİTAŞ (Türkiye Tarımsal Araştırmalar Dergisi, 2018)
Plants survive in unfavorable environmental conditions by developing some strategies. One of these strategies is dormancy. This article was prepared to provide information about the summer dormancy of plants in summer. Summer dormancy is a type of endo-dormancy that plants have. It is very difficult to determine that the plant has endo-dormant by phenotype. For this reason, it is necessary to determine the type of dormancy. As a result of the studies, summer dormancy was determined in many plant species belonging to different families including Poaceae family. In order to increase both the production of forage crops and the yield of grasslands, the perennial cool season grasses should be cultivated. While plants having summer dormancy may lost all or some of the aboveground parts, underground meristematic tissues can continue their vitality. Therefore, plants can survive under extreme conditions. However, the yields during summer are rather low. For this reason, dormancy characteristics of the plants should be clearly defined and the cultivation area and cultural practices should be chosen correctly.